2012
DOI: 10.1097/ico.0b013e3181dc81d2
|View full text |Cite
|
Sign up to set email alerts
|

Thermocautery for Inferior Conjunctivochalasis

Abstract: Thermocautery is a simple and effective treatment for symptomatic inferior conjunctivochalasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…The operation time is very short and can be performed in places like outpatient clinics that do not require much equipment [48]. Nakasato S et al showed that thermocautery is a simple and effective treatment for symptomatic inferior CCh [50].…”
Section: Subconjunctivalmentioning
confidence: 99%
“…The operation time is very short and can be performed in places like outpatient clinics that do not require much equipment [48]. Nakasato S et al showed that thermocautery is a simple and effective treatment for symptomatic inferior CCh [50].…”
Section: Subconjunctivalmentioning
confidence: 99%
“…Furthermore, it is also supported by the experimental data showing excessive degradation of the extracellular matrix by matrix metalloproteinases (MMPs) under pro-inflammatory cytokines. 26,27 As of now, a number of surgical procedures have been advocated to treat CCh such as scleral fixation suture, 28 crescent bulbar conjunctival excision with direct closure, 6,29 resection combined with inferior peritomy and radial relaxing incisions, 29 excision with AM transplantation, 17,18,30 cauterization/laser coagulation with or without excision 31,32 and subconjunctival fibrin sealant followed by excision. 33 A majority of these procedures focus on elimination of conjunctival folds close to the tear meniscus.…”
Section: Discussionmentioning
confidence: 99%
“…38,45 Strategies incorporating fibrin glue, suture fixation to the sclera, amniotic membrane placement, and thermal cautery have also been described. 37,40,46,47 The presence of an enlarged caruncle, a megalocaruncle, can be considered a form of CCh, and may cause functional lacrimal drainage obstruction. 48 Anatomically, a megalocaruncle is an enlarged caruncle that extends to or beyond the inferior lacrimal punctum.…”
Section: Blickmentioning
confidence: 99%